Therapeutic effects of Hominis placenta herb-acupuncture in adjuvant-induced arthritis rat - MiJung Yeom; Ji-Eun Kang; Dae-Hyun Hahm; Hi-Joon Park; EunJoo H.Lee; In-Sop Shim; Hye-Jung Lee (Korean Pharmacopuncture Institute, 2002)
Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease, characterized by leukocyte infiltration, a chronic inflammation of the joint, a pannus formation and the extensive destruction of the articular cartilage and bone. Several proinflammatory cytokines such as tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β) and interleukin 6 (IL-6) have been implicated in the pathological mechanisms of synovial tissue proliferation, joint destruction and programmed cell death in rheumatoid joint. In the Korean traditional medicine, Hominis placenta (HP) as an herbal solution of herb-acupuncture has been widely used to treat the inflammatory diseases including RA. In order to study the medicinal effect of HP herb-acupuncture on rheumatoid joint, an adjuvant-induced arthritis (AIA) was generated by the injection of 1.5 mg of Mycobacterium tuberculosis, emulsified in squalene, to the base of the tail of Spraque-Dawley (SD) rats. After onset stage of polyarthritis, HP was daily injected to the Zusanli (ST36) acupuncture points in both of rat lags and the expression patterns of cytokines such as TNF-α, IL-1β, and IL-6 at the knee joint were analyzed using immunostaining and RT-PCR. The HP herb-acupuncture was found to be effective to alleviate the arthritic symptoms in adjuvant-induced arthritic rats as regards the joint appearance and the expression profiles of inflammatory cytokines. In conclusion, therapeutic effects of HP herb-acupuncture on the rat with AIA might be related to anti-inflammatory activities of the hurb-acupuncture.